Cohort Profile: The Australian Parental Supply of Alcohol Longitudinal Study (APSALS). (6th May 2015) - Aiken, Alexandra; Wadolowski, Monika; Bruno, Raimondo; Najman, Jackob; Kypri, Kypros; Slade, Tim; Hutchinson, Delyse; McBride, Nyanda; Mattick, Richard P
Abstract: The Australian Parental Supply of Alcohol Longitudinal Study (APSALS) was established in 2010 to investigate the short- and long-term associations between exposure to early parental alcohol provision, early adolescent alcohol initiation, subsequent alcohol use and alcohol-related harms, controlling for a wide range of parental, child, familial, peer and contextual covariates. The cohort commenced with 1927 parent-child dyads comprising Australian Grade 7 school students (mean age = 12.9 years, range = 10.8–15.7 years), and a parent/guardian. Baseline, 1- and 2-year follow-up data have been collected, with > 90% retention, and a 3-year follow-up is under way. The data collected include child, familial, parental and peer factors addressing demographics, alcohol use and supply, parenting practices, other substance use, adolescent behaviours and peer influences. The cohort is ideal for prospectively examining predictors of initiation and progression of alcohol use, which increases markedly through adolescence.